THE EFFECTIVENESS OF CELL PHONE-BASED MENTORING THROUGH SMS ON DIET COMPLIANCE AMONG TYPE 2 DIABETES MELLITUS (T2DM) PATIENTS - ratna dewi; Rostinah Manurung; Sarmaida Siregar (International Journal of Nursing and Health Services (IJNHS), 2019)
Appropriate diet and physical exercise is part of diabetes management. The role of health professionals is critical to regulating the lifestyle of type 2 DM patients. The study aimed at examining the effectiveness of cell phone-based mentoring on dietary compliance. A quasi-experimental study design, pre and post-test equivalent with the control group. The research was conducted at Bromo Medan Health Center. We recruited 84 diabetic patients and divided into the experimental and control group. The findings showed there was a positive effect on the patients in the experimental group who received the program than patients in the control group who did not receive the application. This strategy is essential and recommended to apply in the routine diet at home. Keywords: short message service (SMS), diet compliance, type 2 diabetes mellitus